Characteristics of Patients Admitted to Florida Hospitals for Cardiovascular Diseases - Diana Maria Dávalos; WayWay M. Hlaing (University of North Florida, 2008)
The present study evaluated the variations in demographic and clinical characteristics of patients hospitalized for cardiovascular diseases (CVD) in Florida hospitals in 2005. Using the 2005 data from the Florida Agency for Health Care Administration, patients admitted for any CVD were extracted by using the International Classification of Diseases, 9th edition (ICD-9) codes. Of all patients (N=2,534,641) hospitalized in 2005, about 17.7% (n=450,559) were admitted for CVD. There were nine distinct diagnosis groups for CVD and about 33.2% and 31.8% of patients were admitted for other forms of heart disease (OHD) and ischemic heart disease (IHD), respectively. Cerebrovascular disease or accident (CVA) was the third leading cause of CVD hospitalization in 2005. There were more women than men in all CVD categories except in IHD, OHD, and diseases of the arteries, arterioles, and capillaries (DAAC). Most patients in each group were whites, federal or Medicare beneficiaries, and likely to be admitted for emergency reasons. About 5% of patients with CVA and chronic rheumatic heart disease (CRHD) died in hospitals. Compared to other groups, more patients with CHRD and CVAs were discharged to other facilities for continued care. Patients with acute rheumatic fever (ARF) had the longest hospitals stays (mean=9.2 days) and those with IHD had the shortest (mean=4.2 days).